A decision support model to optimise the operation and maintenance strategies of an offshore renewable energy farm. (15th November 2017) - Rinaldi, G.; Thies, P.R.; Walker, R.; Johanning, L.
Abstract: In order to accelerate the access into the energy market for ocean renewables, the operation and maintenance (O&M) costs for these technologies must be reduced. In this paper a reliability-based simulation tool for the optimization of the management of an offshore renewable energy (ORE) farm is presented. The proposed tool takes into account the reliability data of the simulated devices and estimations on the energy produced to create a series of results in terms of availability and maintainability of the farm. The information produced supports operational and strategic decision making regarding the O&M for offshore farms. A case study simulating a conceptual tidal energy project, consisting of an array of two tidal turbines located off the north coast of Scotland, is presented to show some of the results achievable with this model. The proposed methodology, although adopted for a tidal farm here, is generally applicable to other kinds of ORE farms. Highlights: A reliability-based simulation tool for offshore renewables is proposed. The information obtainable supports the decision making practice for farm owners, farm operators and device developers. Focus is given towards the optimization of the power production, the O&M planning and the consequent reduction of final cost of energy. A case study is presented for a conceptual tidal energy project.